IMPACTS OF DUMPSITE ON SOIL AND GROUNDWATER QUALITY: A CASE STUDY OF ERINFUN COMMUNITY, ADO EKITI, SOUTHWESTERN NIGERIA - F., F. Akinola (Zibeline International, 2021)
Groundwater pollution has increased as a result of poor waste disposal practices in developing countries. The purpose of this study was to determine the levels of physicochemical parameters and heavy metal concentrations in order to investigate the impact of dumpsites on groundwater and soil quality in Erinfun community. Four (4) water samples were collected hand dug well and four (4) soil samples designated Ss1 to Ss4 were collected at distances of 10, 20, 30 and 40 m, respectively, away from the waste dumpsite. Physicochemical parameters and traces such as odour, colour, taste and temperature, as well as Biochemical Oxygen Demand, Chemical Oxygen Demand, Dissolve Oxygen, Total Dissolve Solid, pH, and chloride were measured in collected water samples. Collected soil samples were also analyzed for heavy metals such as Magnesium, Zinc, Iron, Chromium, and Lead. All the physical parameters of the water samples analysed were found not to be within the acceptable limit of World Health Organization and Nigerian Standard of Drinking Water Quality standards. The chemical constituents tested were within the acceptable limit of World Health Organization and Nigerian Standard of Drinking Water Quality except for the Biochemical Oxygen Demand, Chemical Oxygen Demand and Dissolve Oxygen of water samples 1 and 2, respectively. The concentration of trace metals in water sample test were within health limit except for Magnesium and Iron which has the highest concentrations in water sample 1 at 10 m away from dumpsite (61.00 mg/l and 0.46 mg/l). Consequently, open dumpsites are discouraged, and constructed standard landfills with appropriate monitoring guidelines are recommended.